PELATIHAN INSTALLASI DAN OPERASIONAL BLENDED LEARNING UNTUK ADMIN FAKULTAS - Zamzami Zamzami; Yogi Yunefri; Didik Siswanto (Jurnal Pengabdian Masyarakat Multidisiplin, 2018)
The Learning process at Faculty of Education and Vocational Education (FKIP)) and the Faculty of Administrative Sciences (FIA) lecturers has been providing materials by displaying lecture materials using projector, as well as writing lecture materials on the blackboard. The student quiz is conducted after several meetings, the students are required to work on and complete the quiz given by the lecturer and then immediately collected after the time is up or finished. To give and collect the task, the lecturer give it during the lecture period and there are also lecturers who give the task at the end of the lecture after the lecturer delivered the lecture material, and the collection is done during the meeting in the class or on the next day schedule in the form of hardcopy so that the lecturer must certain to correct it. To face the problems faced by the Faculty of Education (FKIP) and Faculty of Administrative Sciences (FIA) the authors suggest with the use of electronic-based learning media that is Blended Learning.